2006
DOI: 10.1063/1.2204574
|View full text |Cite
|
Sign up to set email alerts
|

ZnO thin-film transistors with polycrystalline (Ba,Sr)TiO3 gate insulators

Abstract: The electrical characteristics of ZnO thin-film transistors with high-k ͑Ba, Sr͒TiO 3 gate dielectrics are presented. The ZnO and ͑Ba, Sr͒TiO 3 thin films were deposited on Pt, exhibiting polycrystalline characteristics. The thin-film devices demonstrated transistor behavior over the range of 0-10 V with a stable threshold voltage of approximately 1.2 V. The field effect mobility, subthreshold slope, and on/off ratio were measured to be 2.3 cm 2 V −1 s −1 , 0.25 V / decade, and 1.5ϫ 10 8 , respectively. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 11 publications
1
71
0
Order By: Relevance
“…8 There is a significantly vibrant literature on ZnO channel TFTs deposited with different methods such as physical vapor deposition, chemical vapor deposition, chemical solution deposition, molecular beam epitaxy, and atomic layer deposition (ALD). [1][2][3][4][9][10][11][12] The on-to-off current ratios, I on /I off , of these devices range from 10 to 10 8 with reported electron mobility values between 0.031 and 56.43 cm 2 /V-s. 2,[13][14][15][16][17] Among all these techniques, ALD is promising due to the low growth temperature, large area uniformity, precise thickness control, highly conformal deposition, and scalability to roll-to-roll processes. Low temperature processing is very crucial for compatibility with flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
“…8 There is a significantly vibrant literature on ZnO channel TFTs deposited with different methods such as physical vapor deposition, chemical vapor deposition, chemical solution deposition, molecular beam epitaxy, and atomic layer deposition (ALD). [1][2][3][4][9][10][11][12] The on-to-off current ratios, I on /I off , of these devices range from 10 to 10 8 with reported electron mobility values between 0.031 and 56.43 cm 2 /V-s. 2,[13][14][15][16][17] Among all these techniques, ALD is promising due to the low growth temperature, large area uniformity, precise thickness control, highly conformal deposition, and scalability to roll-to-roll processes. Low temperature processing is very crucial for compatibility with flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
“…1 The tunable conductivity of ZnO thin film makes it a very promising candidate for both passive and active electronic applications. [2][3][4] Although zinc oxide TFTs with good field-effect mobility have been reported using various deposition techniques, [5][6][7][8][9][10] the stability of ZnO and other oxide-based TFTs under gatebias stress is a major concern for display applications. [11][12][13][14] Further, the increased temperature of display devices due to prolonged use or operation under harsh conditions can significantly shift the threshold voltage of the pixel-TFTs, 14,15 which would affect the performance of the corresponding device.…”
mentioning
confidence: 99%
“…La 2 O 3 has a very high subthreshold slope of 1.2 V/decade and hence the electrical performance will be poorer in comparison to others. Figure 5 shows the relationship between threshold voltage and dielectric constant based on the data obtained in [5][6][7][8][9][10][11]. The values are highly scattered as threshold voltage depends on some other factors also.…”
Section: Resultsmentioning
confidence: 99%
“…Hence we found that HfO 2 , Y 2 O 3 , La 2 O 3 and ZrO 2 are the possible candidates that satisfy the constraints of high dielectric constant and a considerable band gap and conduction band offset. Figure 4 shows the relationship between subthreshold slope and and dielectric constant based on the data obtained in [5][6][7][8][9][10][11]. It can be observed that all the materials except La 2 O 3 have subthreshold slope lying in the range of .18-.23 V/decade.…”
Section: Discussionmentioning
confidence: 99%